The Effect of Wireworm Agriotes spp. in Many Types of Potatoes - Yonus, May I.; Hameed, Aliaa Abdul Aziz; Mahdii, Beadaa Abdalqader (Iraqi Journal of Science, 2018)
The present study demonstrate the infection (injury and damage) of wireworm on potato crop in spring and autumn season. This study was conducted in Abu- Greeb fields in Baghdad– Iraq during 2009 – 2010 In order to assessment the damage caused by wireworm Agriotes spp. on four type of growing Solanum tuberosum crop (Rodeo, Lotona, Bleni, Deseri) in spring and autumn season. The results of this study showed that Agriotes spp. was more damage in spring season more than autumn season. Percentage of the numbers of damage potato tuber to the four types was 1.81, 4.87, 6.66, 8.33 % respectively. While it was 6.55, 3.63, 10.52, 9.09 % total weight of Rodeo, Lotona, Bleni, Deseri , respectively. The Rodeo type was more injury in spring season with ratio of 11 tuber number. The result showed that the potato was damage in spring season more than autumn season and this may be due to the presence of the larvae near soil surface that liege with temperature during season. Also may be due to size of potato tuber which cultured large tuber with wide surface area be more damaged and injury.